RENDERING CULTURAL ELEMENTS IN BANYUMASAN BEGALAN: A TRANSLATION STUDIES PERSPECTIVE - Asrofin Nur Kholifah (Faculty of Humanities, Universitas Jenderal Soedirman, 2018)
Begalan is one of Banyumas traditions generally held in wedding ceremony in which involves several processions. As an oral tradition, this is undoubtedly rich of moral values to guide the local people in life over generation. Moreover, it contains symbolic meanings of Javanese philosophy. Begalan, thus, in the perspective of Banyumas people becomes tatanan (norm), tuntunan (guidance), and tontonan (performance) simultaneously. In regard to this, cultural-bound elements become inevitable issue particularly if it is viewed through translation studies. Accordingly, this paper is aimed at describing several cultural elements which are used in this tradition. Then some strategies dealing with transposing local cultures embodied in those elements are proposed. Among them are transference, paraphrase, and translation by icon. In the process of translating, a process of rewriting message, an appropriate strategy should be taken into account for the sake of retaining embodied moral values in each element. Moreover, the translator’s creativity becomes precious skill in coping with those elements. A creative translator would be able to produce a closest equivalence to reach the same effect as original one. In particular, this brings about the concept of begalan not only comprehended through its exhibition but also through written materials. In general, those strategies are possibly applied to transfer some similar texts for students in their learning, for teachers to teach translation and for translator for practice.